THE BACKWARD ART OF TEACHING ACCOUNTING. - Myer, John N. (The Accounting Review, 1946)
When the accountancy graduate obtains his first job it is most likely that his employer will tell him to forget what he learned in college and to get adjusted to accountancy as it is practiced. This statement by the employer is, of course, only a conversational exaggeration, for he does not really mean that everything taught in the accountancy courses is wrong. But from observing the equipment of the college graduates in his employ he gets a pretty definite impression that what goes on in college courses is far from what might be desired. It is the opinion of the writer that there are two causes for the current discrepancy between the academic world and the business world, faulty text material, and lack of standards for teacher qualifications. The existing textbooks either were written about a quarter of a century ago or were modeled after those written at that time. The fundamental defect in these texts is that they are governed by the fallacies inherent in the balance-sheet approach. The most important qualification of a teacher of accountancy is the ability to explain and expound accountancy as it is practiced.